2015
DOI: 10.1093/chromsci/bmu223
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Related Substances of Perindopril Tert-Butylamine Using a Novel Stability Indicating Liquid Chromatographic Method

Abstract: A novel stability indicating gradient reverse-phased high-performance liquid chromatographic method has been developed for the quantification of impurities of perindopril tert-butylamine (PER) in pharmaceutical dosage form. Separation of the active substance and its known (Impurities B, C, D, E, F) and unknown impurities was achieved on a BDS Hypersil C18 column (250 mm × 4.6 mm, 5 µm), thermostated at 70°C, using a mobile phase comprised of aqueous solution of sodium 1-heptanesulfonate adjusted to pH 2 with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The application of ion‐pairing reagents for the separation of hydrophilic substances in reversed‐phase high‐performance liquid chromatography (RP HPLC) has been extensively studied . Previous reports described the successful use of sodium 1‐heptanesulfonate as ion‐pairing agent for the separation of many drugs . Due to the ionizable nature of free amino acids (cationic, anionic or even zwitterionic), their separation can also be achieved by ion‐exchange or ion‐pair RP HPLC .…”
Section: Introductionmentioning
confidence: 99%
“…The application of ion‐pairing reagents for the separation of hydrophilic substances in reversed‐phase high‐performance liquid chromatography (RP HPLC) has been extensively studied . Previous reports described the successful use of sodium 1‐heptanesulfonate as ion‐pairing agent for the separation of many drugs . Due to the ionizable nature of free amino acids (cationic, anionic or even zwitterionic), their separation can also be achieved by ion‐exchange or ion‐pair RP HPLC .…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature survey revealed that, only a few analytical methods are available for determination of perindopril arginine and amlodipine besylate in bulk drugs and pharmaceuticals like in vitro dissolution study using high performance liquid chromatography (HPLC), thin-layer chromatography-densitometry, and stability-indicating reverse phase liquid chromatography (RP-LC) methods ( 1 2 3 4 5 6 ). Methods have also been developed for the estimation of perindopril arginine and amlodipine besylate in combination with other drugs simultaneously in bulk drugs and pharmaceutical formulations and in various biological matrices by using visible spectrophotometry, high performance thin layer chromatography (HPTLC), reverse phase high performance liquid chromatography (RP-HPLC), and capillary gas chromatography techniques ( 7 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perindopril with a molecular weight of 368.5 g/mol and Indapamide with a molecular weight of 365.8 g/mol were subjected to basic degradation by 1 N NaOH and heating at 90 °C for 90 min. Although the degradation product was below the detection limit on the UPLC-UV instrument, a Perindopril degradation product was identified and confirmed by UHPLC-QToF-MS analysis as in Figure 4 [ 28 ]. Indapamide was found to be stable towards basic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other degradants were detected by UHPLC-QToF-MS but their concentration was below the detection limit on UPLC-UV. The obtained m / z ratios suggested the degradation products in Figure 6 [ 28 ]. On the other hand, both analytes were found to be stable under the adopted thermal conditions.…”
Section: Resultsmentioning
confidence: 99%